Peran Zakat Dalam Upaya Pemerataan Kesejahteraan Di Indonesia - Cinta Rahmi; Syarifah Hudhriah; Firly Adibha; Muhammad Khairul Luthfi; Qila Husnul Qolbi Al-Um (CV. ITTC INDONESIA, 2024)
The purpose of this research is to find out how the role of zakat in efforts to equalize welfare in Indonesia. This research uses qualitative research methods with a descriptive approach. income inequality is a condition where the level of income between individuals is uneven. Indonesia is one of the countries with the most severe inequality in the world, where the wealth of the four richest people in Indonesia is equal to the wealth owned by 100 million poor people in the country. Thus, income distribution inequality is a major problem that should not be ignored. One of the important teachings of Islam is the guidance that humans strive to live a balanced life, paying attention to the welfare of life in the world and the safety of life in the hereafter. As a prerequisite for the welfare of life in the world is how economic resources can be utilized maximally and correctly within the Islamic framework. From the research conducted, researchers found that zakat can help in terms of reducing income inequality and providing benefits to groups in need. With zakat, the income earned by well-off individuals is distributed to those who are financially underprivileged which is then used to fulfill their needs.